Melia dubia and its Importance: A Review - Goswami, Manika; Bhagta, Shikha; Sharma, Dushyant (International Journal of Economic Plants, 2020)
Melia dubia popularly known as Malabar Neem is a promising multipurpose tree highly suitable for farm forestry and agro forestry for generating higher income per unit area. Melia dubia is one of the fastest growing trees in the world and considered as a money spinning tree of short rotation due to its high demand in pulpwood, plywood and timber industries. It is a good fuel and fodder yielding tree. In addition to this, Melia dubia also has extensive medicinal, pharmacological, ethnomedicinal and conventional properties and uses. The current article reviews literature on importance of Melia dubia for timber industry and medicinal value.